2009
DOI: 10.1002/chem.200901290
|View full text |Cite
|
Sign up to set email alerts
|

Cycloaddition Reactions of Kinetically Stabilized 9‐Silaanthrancene with Polycyclic Aromatic Hydrocarbons

Abstract: A mass of codes: Lysine‐rich silaffin proteins from diatoms guide silica formation by self‐assembly processes. Aided by mass spectrometry, the analysis of 28 posttranslationally modified lysine residues in silaffin‐3 from Thalassiosira pseudonana uncovers an amino acid sequence based code selecting the type of modification. This code may be a key element in the genetic control of species‐specific silica architectures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…As part of our ongoing research projects in the area of novel aromatic compounds, we have already succeeded in the incorporation of a silicon atom into various aromatic ring skeletons by the application of an efficient protecting group, 2,4,6-tris[bis(trimethylsilyl)methyl]phenyl (Tbt), to afford heavier analogues of benzene, naphthalene, anthracene, and phenanthrene. , Studies on their structural and spectroscopic properties together with theoretical calculations indicated that these silaaromatic compounds have much smaller energy gaps between their frontier orbitals than do those of the parent aromatic hydrocarbons, in addition to their high aromaticity. These results clearly show that silaaromatic frameworks are promising for the creation of novel π-conjugated systems containing heavier main-group elements .…”
mentioning
confidence: 99%
“…As part of our ongoing research projects in the area of novel aromatic compounds, we have already succeeded in the incorporation of a silicon atom into various aromatic ring skeletons by the application of an efficient protecting group, 2,4,6-tris[bis(trimethylsilyl)methyl]phenyl (Tbt), to afford heavier analogues of benzene, naphthalene, anthracene, and phenanthrene. , Studies on their structural and spectroscopic properties together with theoretical calculations indicated that these silaaromatic compounds have much smaller energy gaps between their frontier orbitals than do those of the parent aromatic hydrocarbons, in addition to their high aromaticity. These results clearly show that silaaromatic frameworks are promising for the creation of novel π-conjugated systems containing heavier main-group elements .…”
mentioning
confidence: 99%